(untitled) (Latakia University Journal -Basic Sciences Series, 2023)
The current study included a liquid-liquid extraction of the trivalent lanthanum ion by means of the reagent ((3,1-diphenyl-5-(p-nitrophenyl)formazane)), and the effect of various factors was studied on the percentage of extraction and the extraction coefficient, including the pH of the medium. , Mixing the two phases, the concentration of the studied ion, and also the effect of the presence of some competitive positive ions, and the effect of the extraction process in batches, in addition to studying the effect of the ratio of the organic phase to the aqueous phase. The results of this research showed that the best equilibrium time was at 90 minutes, and the best PH degree was at PH = 5. As for the extraction process in batches, the results showed that it was not very effective, so it was better to extract in one batch to save effort and time. The value of the distribution coefficient and the transition ratio increased with the increase in the concentration of the lanthanium ion in the aqueous phase, and this behavior was expected due to the continuous interaction between the ions and the formazan. As for the effect of the presence of some positive ions competing for the lanthanium ion, the greatest effect was the triple chromium ion (Cr3+). In general, and through the results of the research, it is noted that the formazan reagent can be used effectively in the process of extracting ternary lanthanum from aqueous solutions, and later used in extracting it from real samples such as solutions resulting from phosphates and phosphogypsum